Nrf2-mediated adaptive response to methyl glyoxal in HepG2 cells involves the induction of AKR7A2. (5th June 2015) - Li, Dan; Ma, Shuren; Ellis, Elizabeth M.
Highlights: Methyl glyoxal increases the mRNA expression of NQO1, AKR1C3 and AKR7A2 enzymes. AKR7A2 protects HepG2 cells against methyl glyoxal toxicity. Methyl glyoxal activates Nrf2 by inducing its translocation to the nucleus. Nrf2 is critical in mediating methyl glyoxal induced expression of protective genes. Abstract: Methyl glyoxal (MG), a highly reactive dicarbonyl metabolite, causes a range of changes within the cell. It forms adducts with DNA and protein and contributes to the progression of several diseases as well as causing hepatic damage. In this study, we have used human hepatoma (HepG2) cells as a model to investigate the induction of protective enzymes in response to MG exposure. We have shown that treating HepG2 cells with sub-lethal concentrations of MG increases the level of NADPH:quinone oxidoreductase (NQO1) mRNA by 4.5-fold, AKR1C3 mRNA by 14-fold and AKR7A2 mRNA by 4-fold. Levels of AKR7A2 protein are increased by 2.1- and 1.8-fold following 9 h and 24 h exposure of cells to 50 μM MG. The role of AKR7A2 in protecting HepG2 cells against MG toxicity was further investigated using specific siRNAs against AKR7A2 and Nrf2. Knockdown of AKR7A2 in HepG2 shows that AKR7A2 is responsible for up to 50% of the protection against MG toxicity in HepG2 cells. We have also shown that MG was able to induce the translocation of the transcription factor Nrf2 to the nucleus. HepG2 cells in which Nrf2 had been knocked down exhibited decreased NQO1 and AKR7A2 mRNA levels compared to control cells. In conclusion, these findings indicate that protective enzymes are significantly up-regulated in response to low concentrations of MG in HepG2 cells and that AKR7A2 contributes to protection against MG-induced toxicity. Nrf2 is critical in mediating MG induced expression of protective genes.